Hyaluronan export through plasma membranes depends on concurrent K+ efflux by Kir channels - Hagenfeld, Daniel; Borkenhagen, Beatrice; Schulz, Tobias (2012)
Hyaluronan is synthesized within the cytoplasm and exported into the extracellular matrix through the cell membrane of fibroblasts by the MRP5 transporter. In order to meet the law of electroneutrality, a cation is required to neutralize the emerging negative hyaluronan charges. As we previously observed an inhibiting of hyaluronan export by inhibitors of K+ channels, hyaluronan export was now analysed by simultaneously measuring membrane potential in the presence of drugs. This was done by both hyaluronan import into inside-out vesicles and by inhibition with antisense siRNA. Hyaluronan export from fibroblast was particularly inhibited by glibenclamide, ropivacain and BaCl2 which all belong to ATP-sensitive inwardlyrectifying Kir channel inhibitors. Import of hyaluronan into vesicles was activated by 150 mM KCl and this activation was abolished by ATP. siRNA for the K+ channels Kir3.4 and Kir6.2 inhibited hyaluronan export. Collectively, these results indicated that hyaluronan export depends on concurrent K+ efflux.
Gesehen am 03.05.2018